Effect of soil amendments, climate and rootstock on tree performance and fruit quality of 'Valencia' orange used for processing - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Agric) Horticultural Science)--University of Pretoria, 2005.